Economic valuation of forest as habitat for elephants: case study at Belum-Temenggor forest complex - Ahmad Zaini, Azniza; Mohd Noor, Mohd Iqbal; Ahmad, Badli Esham; Amir Mustafa, Amira Mas Ayu; Eylen, William V. (Universiti Teknologi MARA (UiTM), 2023)
The conversion of forests to other land uses, such as agriculture or housing, has led to an increase in the interaction between people and elephants that can highly result in human-elephant conflict. This conflict led to various socio-economic losses, such as losses of crop yields and the temporary decline in the tranquillity of villages and fear during the period of the conflict. Conceptually, the value of these losses could be used as a basis for the minimal value of the forest as a habitat for elephants. These studies value the HEC losses using economic valuation methods (replacement cost, change in productivity and contingent valuation methods). A case study of the invasion of the elephant herd from Belum-Temenggor Forest Complex is provided as an illustration. The case study result shows that if the forest is being established as a protected area to conserve elephants, the aggregate value of potential avoided losses from HEC is RM2,977 per villager, and the estimated value for 150 households is RM0.45 million per year.